A STUDY OF THE INFLUENCE OF PET OWNERSHIP ON MENTAL HEALTH ACROSS THREE FAMILY GENERATIONS (Journal of Informatics Education and Research, 2025)
Pet ownership has well been linked with emotional-mental strength, enhanced psychological wellness, and improved social behavior. This literature review dives into the impact of fellow animals on mental health across many generations within families, bringing findings from global studies and upcoming Indian research. Over the world, pet ownership is often linked to reduced levels of anxiety, depression, and loneliness, mainly with dogs especially noticeable for their therapeutic emotional bonds. Impact on multiple generations is clear, with grandparents, parents, and children enjoying visible emotional benefits from pet companionship. The review highlights the role of pets during stressful periods, such as the COVID-19 pandemic, and underscores the emotional resilience fostered by pet companionship. This review supports that the immersion of pets into family life can act as a sustainably doable, culturally adaptable mental health strategy, assuring deeper understanding in both national and global settings.